Multiple Antibiotic Resistance Gene Transfer from Animal to Human Enterococci in the Digestive Tract of Gnotobiotic Mice - Moubareck, C. (American Society for Microbiology, 2003)
It has been proposed that food animals represent the source of glycopeptide resistance genes present in enterococci from humans. We demonstrated the transfer of vanA and of other resistance genes from porcine to human Enterococcus faecium at high frequency in the digestive tract of gnotobiotic mice. Tylosin in the drinking water favored colonization by transconjugants.